Renal dysfunction improves risk stratification and may call for a change in the management of intermediate- and high-risk acute pulmonary embolism: results from a multicenter cohort study with external validation - Romain Chopard; David Jimenez; Guillaume Serzian; Fiona Ecarnot; Nicolas Falvo; Elsa Kalbacher; Benjamin Bonnet; Gilles Capellier; François Schiele; Laurent Bertoletti; Manuel Monreal; Nicolas Meneveau (Critical Care, 2021)
Abstract Background Renal dysfunction influences outcomes after pulmonary embolism (PE). We aimed to determine the incremental value of adding renal dysfunction, defined by estimated glomerular filtration rate (eGFR), on top of the European Society of Cardiology (ESC) prognostic model, for the prediction of 30-day mortality in acute PE patients, which in turn could lead to the optimization of acute PE management. Methods We performed a multicenter, non-interventional retrospective post hoc analysis based on a prospectively collected cohort including consecutive confirmed acute PE stratified per ESC guidelines. We first identified which of three eGFR formulae most accurately predicted death. Changes in global model fit, discrimination, calibration and reclassification parameters were evaluated with the addition of eGFR to the prognostic model. Results Among 1943 patients (mean age 67.3 (17.1), 50.4% women), 107 (5.5%) had died at 30 days. The 4-variable Modification of Diet in Renal Disease (eGFRMDRD4) formula predicted death most accurately. In total, 477 patients (24.5%) had eGFRMDRD4 < 60 ml/min. Observed mortality was higher for intermediate–low-risk and high-risk PE in patients with versus without renal dysfunction. The addition of eGFRMDRD4 information improved model fit, discriminatory capacity, and calibration of the ESC model. Reclassification parameters were significantly increased, yielding 18% reclassification of predicted mortality (p < 0.001). Predicted mortality reclassifications across risk categories were as follows: 63.1% from intermediate–low risk to eGFR-defined intermediate–high risk, 15.8% from intermediate–high risk to eGFR-defined intermediate–low risk, and 21.0% from intermediate–high risk to eGFR-defined high risk. External validation in a cohort of 14,234 eligible patients from the RIETE registry confirmed our findings with a significant improvement of Harrell’s C index and reclassification parameters. Conclusion The addition of eGFRMDRD4-derived renal dysfunction on top of the prognostic algorithm led to risk reclassification within the intermediate- and high-risk PE categories. The impact of risk stratification integrating renal dysfunction on therapeutic management for acute PE requires further studies.